Role modelling of clinical tutors: a focus group study among medical students - Burgess, Annette (BMC Med Educ, 2015)
BACKGROUND: Role modelling by clinicians assists in development of medical students’ professional competencies, values and attitudes. Three core characteristics of a positive role model include 1) clinical attributes, 2) teaching skills, and 3) personal qualities. This study was designed to explore medical students’ perceptions of their bedside clinical tutors as role models during the first year of a medical program. METHODS: The study was conducted with one cohort (n = 301) of students who had completed Year 1 of the Sydney Medical Program in 2013. A total of nine focus groups (n = 59) were conducted with medical students following completion of Year 1. Data were transcribed verbatim. Thematic analysis was used to code and categorise data into themes. RESULTS: Students identified both positive and negative characteristics and behaviour displayed by their clinical tutors. Characteristics and behaviour that students would like to emulate as medical practitioners in the future included: 1) Clinical attributes: a good knowledge base; articulate history taking skills; the ability to explain and demonstrate skills at the appropriate level for students; and empathy, respect and genuine compassion for patients. 2) Teaching skills: development of a rapport with students; provision of time towards the growth of students academically and professionally; provision of a positive learning environment; an understanding of the student curriculum and assessment requirements; immediate and useful feedback; and provision of patient interaction. 3) Personal qualities: respectful interprofessional staff interactions; preparedness for tutorials; demonstration of a passion for teaching; and demonstration of a passion for their career choice. CONCLUSION: Excellence in role modelling entails demonstration of excellent clinical care, teaching skills and personal characteristics. Our findings reinforce the important function of clinical bedside tutors as role models, which has implications for faculty development and recruitment.